2006
DOI: 10.1016/j.molcel.2006.08.020
|View full text |Cite
|
Sign up to set email alerts
|

A Stapled BID BH3 Helix Directly Binds and Activates BAX

Abstract: BAX is a multidomain proapoptotic BCL-2 family protein that resides in the cytosol until activated by an incompletely understood trigger mechanism, which facilitates BAX translocation to mitochondria and downstream death events. Whether BAX is activated by direct contact with select BH3-only members of the BCL-2 family is highly debated. Here we detect and quantify a direct binding interaction between BAX and a hydrocarbon-stapled BID BH3 domain, which triggers the functional activation of BAX at nanomolar dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
410
3
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 356 publications
(436 citation statements)
references
References 53 publications
19
410
3
4
Order By: Relevance
“…This places the interaction surface on Bax at a site distinct from the canonical BH3 interaction groove on prosurvival proteins (Figures 1a and 3). We note that fast exchange reported here is indicative of considerably weaker affinity than the value previously reported by these same authors 26 for the stapled BimBH3/ Bax interaction, 24 nM.…”
Section: A Model For the Stapled Bimbh3/bax Interactioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This places the interaction surface on Bax at a site distinct from the canonical BH3 interaction groove on prosurvival proteins (Figures 1a and 3). We note that fast exchange reported here is indicative of considerably weaker affinity than the value previously reported by these same authors 26 for the stapled BimBH3/ Bax interaction, 24 nM.…”
Section: A Model For the Stapled Bimbh3/bax Interactioncontrasting
confidence: 79%
“…26 In particular, the threefold increase in affinity of the stapled BimBH3 over its parent for Bcl-x L (16 nM compared with 52 nM, respectively, in fluorescence polarization assays) accords with the reported fourfold increase in helicity of the peptide on stapling. Stapled BimBH3 peptides also displayed binding activity for Bax (24 nM) in fluorescence polarization assays but, curiously, no binding to Bax with the unstapled Bim peptide was detected.…”
Section: Stapled Bh3 Peptidessupporting
confidence: 53%
See 1 more Smart Citation
“…While binding of Bid to Bax is relatively easy to observe by coimmunoprecipitation in the presence of non-ionic detergents (Wei et al, 2000;Walensky et al, 2006), binding of Bim to Bax could be shown only for two minor isoforms, BimS and BimAD (Marani et al, 2002), whose physiological significance is also a matter of debate. No direct binding of the major isoform, BimEL, could be observed under the same conditions (Willis et al, 2007), and no binding of any Bim isoform to Bak was ever reported.…”
Section: S131mentioning
confidence: 99%
“…15,16 Upon activation, the proapoptotic family members BAK and BAX can breach the mitochondrial outer membrane (MOM), leading to cytochrome c release, caspase 9 activation and subsequent apoptotic events. Genetic 2,17 as well as biochemical experiments [18][19][20][21][22][23] have indicated that the BH3-only proteins BIM, PUMA, a protease generated BID fragment (tBID), and, in some studies, NOXA can directly bind and activate BAK and/or BAX. To counteract these effects, antiapoptotic BCL2 family members such as BCL2, BCLX L and MCL1 bind and neutralize activated BAX and/or BAK 2,6,16,24 as well as activated or overexpressed BH3-only family members, [25][26][27][28][29][30] thereby preserving MOM integrity.…”
mentioning
confidence: 99%